2021
DOI: 10.21697/sp.2021.21.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Przegląd kryteriów diagnostycznych, cech i typów osobowości borderline wraz z próbą ich porządkowania

Abstract: Zaburzenie osobowości z pogranicza (borderline) jest jednym z najbardziej rozpowszechnionych zaburzeń, a jednocześnie dość problematycznym w diagnozie, na co wskazywały kolejne edycje DSM i ICD. Od dawna wykazywano heterogeniczność osobowości borderline. Zasadniczo pokazywano ją przy pomocy dwóch uzupełniających się podejść: (1) skoncentrowanego na zmiennych, gdzie wyodrębniano czynniki oraz (2) skoncentrowanego na osobach, w którym identyfikowano typy jako konfiguracje zmiennych. W niniejszym artykule zapreze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
5
1
Order By: Relevance
“…As shown in the extensive literature, clinicians and researchers indicate a rather diversified clinical picture of BPD [35]. However, this borderline heterogeneity is not reflected in the results of our research.…”
Section: Discussioncontrasting
confidence: 62%
“…As shown in the extensive literature, clinicians and researchers indicate a rather diversified clinical picture of BPD [35]. However, this borderline heterogeneity is not reflected in the results of our research.…”
Section: Discussioncontrasting
confidence: 62%
“…Previous research shows that BPD is characterized by considerable heterogeneity (Brud, 2021). For instance, Brud and Cieciuch (2023) BPD is characterized by high emotional sensitivity (reflected by high harm avoidance; e.g., Joyce et al, 2003), and since prior research suggests that it may have different personality backgrounds (i.e., internalizing and externalizing; e.g., Eaton et al, 2011), it is presumable that BPD may also have different levels and mobilization of endogenous drive.…”
Section: Current Studymentioning
confidence: 99%
“…Accordingly, people with BPD often report the following symptoms: dynamically changing emotions, irritability, anxiety, difficulty controlling anger, sensitivity to rejection, a shaky self-image, a sense of emptiness, paranoid thoughts during times of severe stress, difficulties in defining sexual preferences, self-harm, or suicide attempts (Gunderson et al, 2018;Lieb et al, 2004). In addition, BPD shows a high level of comorbidity with a number of other psychiatric disorders, especially at the level of internalizing (e.g., anxious, fragility, despondence, and avoidance) and externalizing dimensions (e.g., dysregulated anger, antisocial, autonomous, and manipulativeness; Brud, 2021;Brud & Cieciuch, 2023;Eaton et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a theoretical review, Brud (2021) identified 37 borderline models based on both dimensionality and BPD typology. He distinguished 59 individual units of meaning and finally formed them into eleven semantic-consistent domain-groups.…”
Section: Borderline Personality and Its Heterogeneitymentioning
confidence: 99%